VALENCY AND SYNTACTICAL RELATION IN BIMANESS - Sri Satyawati, Made; Artawa, I Ketut; Pastika, I Wayan; Sutjaja, I Gusti Made (e-Journal of Linguistics, 2009)
This study presents the findings and descriptions of the replies to severalproblems that have not been completely and deeply discussed in the researchespreviously conducted on Bimanese. The problems are related to micro-linguistic factors,namely valency and syntactical relation in Bimanese. Both deductive and inductiveapproaches were applied to obtain satisfactory results. The main theory employed in thisstudy is Role and Reference Grammar Theory (RRG) by Van Valin and J. Lapolla. It wasemployed to completely analyze the collected data in accordance with the problemsproposed in this research, and the inductive approach was employed to analyze the datain order to get novelties.In this study, clause structure is given the first priority to discuss, followed by thediscussion on operator, voice markers, nominalizers, and definiteness. Based on thepredicate category, the clause in Bimanese can be constructed with the constituents thatare under the categories of verb, noun, adjective, number, and adverb (prepositionalphrase). Based on the clause analysis, it has been found that in Bimanese there are severaloperators, each of which has different functional boundary in marking the clausemeaning. One operator may only sign nucleus, core (nucleus and argument), or core andperiphery. Bimanese has also been identified to have four linguistic states expressed byverbs that are made to make sense based on state (Aktisontrat), achievement, andaccomplishment. RRG classifies verbs into ten instead of four. However, in this study, tomake the analysis easier, verbs are classified into four. The predicate in Bimanese can beboth serial verbs and secondary verbs. It has also been found that the mechanism ofchange in valency is marked by the attachment of markers to the verbs resulting incausativity, applicativity, and resultivity. From those syntactical constructions, thesyntactical relation in Bimanese can be clearly identified. The discussion on syntacticalrelation starts with SUBJ and OBJ followed by word orders. The word orders found inBimanese are SPO, adposition of PREP-N, N-G, N-Adj, N-Dem, and question wordposition. In addition, four voices have also been identified in Bimanese. They are active,passive, middle, and antipassive.
Keywords: morphosyntax, valency, syntactical relation, operator, state, aktionsart, lexical representation, thematic relation, voice, serial verbs, secondary PRED.